Intra-Articular Injection of Human Bone Marrow–Derived Mesenchymal Stem Cells in Knee Osteoarthritis: A Randomized, Double-Blind, Controlled Trial - Bong-Woo Lee; Jennifer Jooha Lee; Joon-Yong Jung; Ji Hyeon Ju (Cell Transplantation)
To assess the impact of a single intra-articular (IA) injection of bone marrow–derived mesenchymal stem cells (BM-MSCs) in patients with knee osteoarthritis (OA), a randomized, double-blind, placebo-controlled study was conducted. The study included 24 patients with knee OA who were randomly assigned to receive either a single IA injection of BM-MSCs or normal saline. Changes in the visual analog scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Knee Injury and Osteoarthritis Outcome Score (KOOS) after IA injection were assessed at 3, 6, 9, and 12 months. Magnetic resonance imaging (MRI) with T2 mapping sequences was conducted for knee cartilage assessment at baseline and at 3 and 12 months. The MSC group showed between-group improvement in WOMAC (–5.0 ± 3.6 vs. –0.1 ± 5.5, P = 0.02) and KOOS (23.9 ± 18.3 vs. 7.2 ± 15.9, P = 0.028) scores at 9 months compared with the control group. The MSC group exhibited a less sharp increase in the mean T2 value of the medial compartment than the control group at 12 months, with no serious adverse events observed during follow-up. A single IA injection of allogeneic BM-MSCs provided satisfactory pain relief for patients with knee OA compared with the control group at 9 months. Quantitative T2 MRI mapping of the cartilage showed that IA BM-MSCs could have a preventive effect on OA progression for 12 months. Our findings suggest the potential of allogeneic BM-MSCs IA injection as a pain-relieving and disease-modifying treatment for patients with knee OA in the outpatient setting.